2020
DOI: 10.1038/s41433-020-01170-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of suprachoroidal haemorrhage drainage with and without vitrectomy: a 10-year study

Abstract: Purpose The management of suprachoroidal haemorrhage (SCH) remains a challenge. We aimed to analyse and discuss the safety and efficacy outcomes of SCH drainage surgery over a 10-year period in one of the largest tertiary centres in the UK. Methods: Retrospective observational study of consecutive patients who underwent SCH drainage in Manchester Royal Eye Hospital over a 10-year period (from 2008 to 2018). Safety and efficacy were assessed by analysing surgery-related complications and functional and anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This assumption is partly supported by the lack of known systemic or ocular risk factors of SCH in our patients and also their recent evident infection with COVID‐19. In the same setting, we had a rate of approximately 0.03% for intraoperative SCH during phacoemulsification in the pre‐COVID‐19 era (all in patients with known risk factors, systemic risk factors include old age and arteriosclerosis, coagulation disorders, vascular hypertension, diabetes mellitus, intraoperative tachycardia, and ocular risk factors include high myopia, glaucoma, previous vitrectomy, pseudophakia, and aphakia 9 ), further increasing our suspicion of COVID‐19 as a predisposing factor for SCH in patients mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is partly supported by the lack of known systemic or ocular risk factors of SCH in our patients and also their recent evident infection with COVID‐19. In the same setting, we had a rate of approximately 0.03% for intraoperative SCH during phacoemulsification in the pre‐COVID‐19 era (all in patients with known risk factors, systemic risk factors include old age and arteriosclerosis, coagulation disorders, vascular hypertension, diabetes mellitus, intraoperative tachycardia, and ocular risk factors include high myopia, glaucoma, previous vitrectomy, pseudophakia, and aphakia 9 ), further increasing our suspicion of COVID‐19 as a predisposing factor for SCH in patients mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…More recent retrospective studies performed at other institutions reported differences in their cohort composition, but had comparable findings to the current study. 24 Qureshi et al performed a retrospective analysis of 20 patients who underwent drainage with or without vitrectomy for SCH. 24 The most common cause of SCH within their cohort was phacoemulsification (35%, 7/20), and the series included 2 cases of traumatic SCH.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Qureshi et al performed a retrospective analysis of 20 patients who underwent drainage with or without vitrectomy for SCH. 24 The most common cause of SCH within their cohort was phacoemulsification (35%, 7/20), and the series included 2 cases of traumatic SCH. External drainage alone was performed in 55% (11/20), while 45% (9/20) had combined PPV and drainage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the majority of cases of phacoemulsification-related SCH tend to be limited; thus, medical management may be enough to achieve good visual outcomes [ 33 , 34 ]. Untreated SCH can lead to devastating consequences, including vision loss and phthisis bulbi [ 35 ]. Isolated cases of the spontaneous resolution of massive SCH with good visual outcomes have been reported; however, the prognosis of massive SCH is typically disappointing.…”
Section: Managementmentioning
confidence: 99%